Aplikasi Pendataan Peredaran Resep Obat dan Monitoring Sumber Daya pada Dinas Kesehatan Kota Banjarmasin - Barry Saputra Oktopiandi Anshari (Journal Information Technology Trends (JITRENDS), 2026)
The Health Office of Banjarmasin City bears a strategic responsibility for supervising medical prescription distribution and managing public healthcare facility (faskes) resources. However, the conventional workflow relies on manual physical recording and periodic email reporting, resulting in delayed real-time monitoring, higher risk of document loss, and inefficiencies in compiling data for medical personnel (doctors, nurses, pharmacists), regional property assets (BMD), and pharmaceutical stock. This research aims to develop a Web-Based Prescription Distribution and Resource Monitoring Application to integrate workflows between the Health Office and regional health service facilities across Banjarmasin. The software development adopts the Waterfall model comprising software engineering, requirements analysis, design, coding, testing, and maintenance. System modeling was constructed using Unified Modeling Language (UML) including Use Case, Activity, and Class Diagrams. The system was implemented using PHP and MySQL. Functional evaluation via Black Box Testing confirmed that all operational modules—including user authentication, master data registry, prescription records, asset request approvals, and analytical reporting—operate reliably and effectively.